Analysis of Leachate of Soil Water Pollution Using Geo-electrical Methods in Final Processing Place (TPA) Regional Sarbagita - Sugestiani, Ni Kadek; Sukarasa, I Ketut; Putra, I Ketut (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
A research about analysis of leachate of soil water pollution using geo-electrical methods in final processing place (TPA) regional sarbagita has been conducted. The measurements were made on 4 tracks by using a Naniura NDR 300HF resistivity meter. The results show on track 1 and track 2 indicate there is a leachate with a resistivity value ranging from 2.67 to 5.74 ?m and 3.15 to 9.19 ?m respectively, on track 3 indicate that the distribution of leachate has decreased compared to paths 1 and 2, on the 3 leachate path there are only certain points with resistivity values ranging from 6.57 to 9.66 ?m. Measurement results on track 4 the resistivity is greater than 10 ?m, this indicates that on track 4 there is no leachate pollution. The results of the analysis of well water samples which are located right on tracks indicating the content of BOD (biochemical oxygen demand), COD (chemical oxygen demand), Cyanide (CN), Lead (Pb), E. coli and coliform which exceeded the quality standard limits.